2022
DOI: 10.1021/acs.molpharmaceut.2c00564
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Reinforced Tough Hydrogel as a Versatile Platform for Pharmaceutical Drug Delivery: Preparation and in Vitro Characterization

Abstract: Natural polymer-based hydrogels are excellent for encapsulating hydrophilic drugs, but they are mechanically weak and degrade easily. In this communication, we exploit the electrostatic interaction between nanosilicates (nSi) and gelatin methacrylate (GelMA) to form a mechanically tough nanocomposite hydrogel for pharmaceutical drug delivery. These hydrogels, prepared at subzero temperatures to form cryogels, displayed macroporous structures, which favors cell infiltration. The designed tough cryogel also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…A robust mechanical strength helps in maintaining the structural integrity of the patch. Adding inorganic fillers, such as nanoparticles, to the hydrogels may increase their mechanical strength 16 . The addition of another polymeric network can also increase the mechanical strength of the hydrogels 33 .…”
Section: Physicochemical Strategies For Hydrogel Patch Adhesion To We...mentioning
confidence: 99%
See 2 more Smart Citations
“…A robust mechanical strength helps in maintaining the structural integrity of the patch. Adding inorganic fillers, such as nanoparticles, to the hydrogels may increase their mechanical strength 16 . The addition of another polymeric network can also increase the mechanical strength of the hydrogels 33 .…”
Section: Physicochemical Strategies For Hydrogel Patch Adhesion To We...mentioning
confidence: 99%
“…Additionally, the diameter of the tip has a great impact on skin penetration. It has been found that a tip diameter below 15 μm yields the best results 16,57 . Recently, Han et al.…”
Section: Advanced Hydrogel Fabrication Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biobased nanoparticles can also be delivered with polymeric scaffolds to promote tissue regeneration by providing a suitable platform for cell attachment, cell–cell interaction, and cell modulation. Such polymeric scaffolds comprise of three-dimensional water-swellable hydrogels that can mimic the native extracellular matrices. Advanced fabrication strategies of hydrogels, such as bioprinting, cryogelation, and electrospinning, can be used for preparing biobased-nanocomposite scaffolds for wound healing, bone regeneration, and cardiac therapy, among others. Additionally, such optimal nanocomposite hydrogel design strategies can be computed using machine learning-based approaches .…”
Section: Conclusion Current Limitations and Future Outlookmentioning
confidence: 99%
“…Pristine dynamic hydrogels generally exhibit low osteogenic activity, and imparting osteogenic active nanoparticles, such as black phosphorus, bioactive glass, manganese dioxide and nanosilicates, could be effective in promoting osteogenesis. Clay nanosheets (Na 0.7 Si 8 Mg 5.5 Li 0.3 O 20 (OH) 4 ) are particularly interesting disc-shaped particles with diameters ranging from approximately 25–30 nm and thicknesses of approximately 1 nm. The intrinsic feature of negatively charged on the surface and positively charged at the edge endows clay nanosheets with great binding ability with macromolecules via electrostatic interactions to reinforce hydrogel matrices and also sustainably release bioactive ions, including Si 4+ , Mg 2+ and Li + to further promote osteogenesis. Furthermore, to ensure augmenting bone regenerative results, the reconstruction of vascular networks is critical. , Unfortunately, the expression levels of endogenous cytokines related to angiogenesis are relatively low during bone defect healing . It has been confirmed that the roles of vascular endothelial growth factor (VEGF) to promote the adhesion and proliferation of HUVECs and angiogenesis regulation, however, it suffers several drawbacks including high cost, immunogenic properties and high doses of VEGF that tend to generate similar capillaries in tumor tissues. Remarkably, the QK peptide, an alternative VEGF mimetic peptide, can recapitulate the biological activity of full-length VEGF of the benefits with cost-effective synthesis, promising stability, and poor immunogenicity. , The QK peptide has been proven to effectively promote angiogenesis, re-epithelialization and increase granulation tissue formation during wound closure. , To this end, considering the aforementioned characteristics of dynamic hydrogels and bioactivated factors for bone regeneration, we hypothesize that synergistically harnessing amyloid fibrils, clay nanosheets, and QK peptide to fabricate dual-nanoengineered DNA dynamic hydrogel can achieve biologically active control to induce enhanced angiogenesis and osteogenesis, but such therapeutic hydrogels have not been reported.…”
Section: Introductionmentioning
confidence: 99%